EVALUASI PROGRAM SUKSES UJIAN NASIONAL DI SEKOLAH MENENGAH KEJURUAN 5 JAKARTA (SUATU KAJIAN POLITIK PENDIDIKAN) - Sarkadi Sarkadi (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2015)
This study aims to explain the effectiveness of the National Exam Success program at SMK 5 Jakarta. The results showed that the evaluation is based on the input of the 4 aspects and 22 sub-aspects, which have met the objective standard is 2 aspects and 17 sub-aspects, which do not meet the standards are 2 aspects and 5 sub-aspects. Aspects that meet the standards are aspects of teacher competence and aspects of school atmosphere, while some aspects of sub aspects are still not meet objective standards are aspects of infrastructure and commitment aspect Principal, Teachers, Students and Parents. Based on the sub-evaluation process, from 7 aspects and 14 sub-aspects are four aspects that meet objective standards and 3 aspects which do not meet objective standards. Aspects that meet the standards covering aspects of learners determination, determination homeroom, the responsibility of parents, and istigosyah. Medium aspects which do not meet objective standards covering aspects of the deepening of the material outside of school hours, periodically try out both internally and externally, and providing motivation by motivator. Based on the results of the evaluation sub 4 aspects and 7 sub-aspects, there are two aspects that already meet the standards of objective and two aspects that do not meet an objective standard. Aspects that meet objective standards covering aspects of achievement in the National Examination (UN) and the aspect proceed to private universities (PTS) 20%. While aspects not meet the standards covering aspects of the industry's absorbed 40% and accepted in public universities (PTN) of 40%.